Археологические исследования генуэзской крепости Чембало в 2000-2005 гг. - Дьячков, С.В. (My University, 2005)
S. Dyachkov. Archeological Research of Genoese Fortress Chembalo in 2000–2005 The article is devoted to preliminary total of excavations of «The consular church» and tower ¹ 8 of Genoese fortress Chembalo (Balaklava). The church was located on the territory of the consular castle. During the excavations it was established that in the 14–15th centuries the church was used by inhabitants as a burial vault. When Chembalo was conquered by Ottoman Turks in 1475 the church was reconstmcted and used by the Christian community of the town. The article gives short description of architectural details of the consular castle that were discovered during the excavations. The author characterizes features of the burial place in the church and some findings requiring special research. Excavation of tower ¹ 8 and adjoining area gives reason to believe that the tower covered land approaches to the consular castle. After 1475 the construction was used by town dwellers for household purposes. Reserves of big stone shots found near the tower provide interesting information about the use of powerful missile weapon in the defences of the Genoese fortress.